Deubiquitinase BAP1 is crucial for surface expression of T cell receptor (TCR) complex, T cell-B cell conjugate formation, and T cell activation - Radhakrishnan, Dhwani; Kotulová, Jana; Hofmanová, Lucie; Sithara, Anjana Anilkumar; Turi, Marcello; Žihala, David; Ďurech, Michal; Vrána, Jan; Uleri, Valeria; Niederlova, Veronika; Stepanek, Ondrej; Chyra, Zuzana; et al. (Journal of leukocyte biology, 2024)
The adaptive immune response critically hinges on the functionality of T cell receptors, governed by complex molecular mechanisms, including ubiquitination. In this study, we delved into the role of in T cell immunity, focusing on T cell-B cell conjugate formation and T cell activation. Using a CRISPR-Cas9 screening approach targeting deubiquitinases genes in Jurkat T cells, we identified BAP1 as a key positive regulator of T cell-B cell conjugate formation. Subsequent investigations into BAP1 knockout cells revealed impaired T cell activation, evidenced by decreased MAPK and NF-kB signaling pathways and reduced CD69 expression upon T cell receptor stimulation. Flow cytometry and qPCR analyses demonstrated that BAP1 deficiency leads to decreased surface expression of T cell receptor complex components and reduced mRNA levels of the co-stimulatory molecule CD28. Notably, the observed phenotypes associated with BAP1 knockout are specific to T cells and fully dependent on BAP1 catalytic activity. In-depth RNA-seq and mass spectrometry analyses further revealed that BAP1 deficiency induces broad mRNA and protein expression changes. Overall, our findings elucidate the vital role of BAP1 in T cell biology, especially in T cell-B cell conjugate formation and T cell activation, offering new insights and directions for future research in immune regulation.
Keywords: signální transdukce; Signal Transduction; Humans; receptory antigenů T-buněk; Jurkat buňky; T-Lymphocytes; nádorové supresorové proteiny; Jurkat Cells; lidé; Ubiquitin Thiolesterase; Tumor Suppressor Proteins; Lymphocyte Activation; B-lymfocyty; Receptors, Antigen, T-Cell; T cell-B cell conjugates; aktivace lymfocytů; BAP1; CRISPR-Cas9 screening; T cell receptor (TCR); B-Lymphocytes; T-lymfocyty; T cell activation; thiolesterasa ubikvitinu